Benzylamide antagonists of protease activated receptor 2 with anti-inflammatory activity. Issue 3 (1st February 2016) - Yau, Mei-Kwan; Liu, Ligong; Lim, Junxian; Lohman, Rink-Jan; Cotterell, Adam J.; Suen, Jacky Y.; Vesey, David A.; Reid, Robert C.; Fairlie, David P.
Graphical abstract: Abstract: Activation of protease activated receptor 2 (PAR2) has been implicated in inflammatory and metabolic disorders and its inhibition may yield novel therapeutics. Here, we report a series of PAR2 antagonists based on C-terminal capping of 5-isoxazolyl-l -cyclohexylalanine-l -isoleucine, with benzylamine analogues being effective new PAR2 antagonists. 5-Isoxazolyl-l -cyclohexylalanine-l -isoleucine-2-methoxybenzylamine (10 ) inhibited PAR2-, but not PAR1-, induced release of Ca 2+ (IC50 0.5 μM) in human colon cells, IL-6 and TNFα secretion (IC50 1–5 μM) from human kidney cells, and was anti-inflammatory in acute rat paw inflammation (ED50 5 mg/kg sc). These findings show that new benzylamide antagonists of PAR2 have anti-inflammatory activity.